Health Literacy and Health Promoting Behaviors Among Karen Older Persons - Prapakorn , Yoottakan; Chintanawat , Rojanee; Tamdee , Decha (Nursing Journal CMU, 2021)
Health literacy is essential for successful health promotion among Karen older persons. This correlation descriptive research aimed to investigate health literacy, health promoting behaviors, and the association between health literacy and health promoting behaviors among Karen older persons. Participants were Karen older persons who resided in Mae Hong Son Province. The 88 participants were selected by using purposive sampling from December 2017 to February 2018. The research instruments used in this study were a demographic data recording form, health literacy questionnaire, and health promoting behaviors of Karen Ethnic Group questionnaire. The data were analyzed using descriptive statistics and the Spearman’s rank correlation. The results showed that the participants had a low level of health literacy and a moderate level of health promoting behaviors. Health literacy had a positive correlation with health promoting behaviors at a moderate level with a statistical significance. These results from this study can determine the benefit of health care professionals in encouraging health literacy and health promoting behaviors among Karen older persons.